Nanofluid Properties For Forced Convection Heat Transfer: An Overview - Azmi, W. H.; K. V., Sharma; R., Mamat; Shahrani, Anuar (Faculty Mechanical Engineering, UMP, 2013)
Nanofluids offer a significant advantage over conventional heat transfer fluids and consequently, they have attracted much attention in recent years. The engineered suspension of nano-sized particles in a base liquid alters the properties of these nanofluids. Many researchers have measured and modeled the thermal conductivity and viscosity of nanofluids. The estimation of forced convective heat transfer coefficients is done through experiments with either metal or nonmetal solid particles dispersed in water. Regression equations are developed for the determination of the thermal conductivity and viscosity of nanofluids. The parameters influencing the decrease in convection heat transfer, observed by certain investigators, is explained.